Corporate Governance, Intellectual Capital, And Earnings Quality: The Moderating Role Of Political Connection In Jordan - Alorayni, Osamah Jamal Dolai (2024)
The separation of ownership from management in corporations has led to the emergence of entities where the interests of multiple related parties may conflict. Financial reports serve as reflections that demonstrate the level of profitability of these companies and provide the primary source of information that can be utilized by various stakeholders in evaluating their performance, predicting their sustainability, cash flow projections, etc. Consequently, earnings quality plays a significant role in attracting investments and fostering economic growth in countries. As jordan is a developing nation striving to attract investments and open up to the world, this study investigates the factors influencing the level of earnings quality, particularly after reviewing previous literature indicating a decline in earnings quality in jordan. The study adopts a research model that aligns with the agency and resource independence theories aimed at bridging the gap and elucidating the contrasting findings of previous literature by examining the roles of both the board of directors and the audit committee characteristics, as outlined in the last modification of the jordanian corporate governance code in 2017. Additionally, the study investigates the impact of intellectual capital components on earnings quality, particularly considering that the jordanian legislature does not require any form of disclosure for intellectual capital by jordanian firms. Furthermore, the study explores the moderating role of political connections on the study's relationships. To